Analisis Semiotika Roland Barthes pada Logo Fana Coffee - Aufa Hanif; Jupriani Jupriani (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This study aims to analyze the meanings embedded in the Fana Coffee logo using Roland Barthes' semiotic theory. The Fana Coffee logo features visual elements such as a bean sprout, soft typography spelling "Fana", and a dominant green color. The research adopts a descriptive qualitative approach through documentation, observation, interviews, and literature review. The analysis reveals that each element in the logo carries denotative, connotative, and mythological meanings. The green color symbolizes freshness and health, the sprout represents strength, simplicity, and adaptability, while the word “Fana” conveys impermanence and peace, aligning with the cozy ambiance of the coffee shop. Overall, the logo effectively reflects the identity and vision of Fana Coffee as a comfortable, natural, and welcoming place for visitors. This study is expected to provide insights for designers in creating meaningful and brand-relevant logos.